Prediction of HLA-DRB1*15 restricted CD4+ epitopes of Indian HIV-1 Gag protein using Insilco approach - JEMMY CHRISTY.H; ALEX ANAND.D (International Journal of Pharma and Bio Sciences, 2014)
Human immunodeficiency virus (HIV) a retrovirus that belongs to the Lentiviridae family, is the causative agent for Acquired Immuno Deficiency Syndrome. Certain “protective” HLA alleles play significant role low viraemia condition like HLA-DRB1*15 allele. An Insilco analysis was adopted to identify Gag epitopes vaccine candidates namely P1-P6 (GLNKIVRMYSPTSIL, LGLNKIVRMYSPTSI, LNKIVRMYSPTSILD, NKIVRMYSPTSILDI, IVRMYSPTSILDIKQ, KIVRMYSPTSILDI) restricted to HLA-DRB1*15 allele would aid significant CD4+ T cell immune response against HIV infection and population coverage among Indian population assessed. Three dimensional structure of epitopes P1-P6 modeled using PEPFOLD, and were tested for their binding affinity towards HLA binding groove using GRAMMX based docking studies resulted with conventional hydrogen bonding,pi-donor,pi-sulfur,carbon hydrogen bonding ,pi-alkyl interaction. Thus the interaction between the screened P1-P6 epitopes exhibiting stability would aid immune response. This computational study of a Gag epitope-based peptide vaccine design for HIV would be helpful in determining novel peptide antigen targets in GAG proteins which need to be validated in vitro and in vivo experiments.